Specific detection of Lettuce mosaic virus isolates belonging to the Most type - Peypelut, M.; Krause-Sakate, R.; Guiraud, T.; Pavan, Marcelo Agenor [UNESP]; Candresse, T.; Zerbini, F. M.; Le Gall, O. (Elsevier B.V., 2004)
Lettuce mosaic virus (LMV)-Most isolates can infect and are seed-borne in cultivars containing the mol gene. A reverse transcription and polymerase chain reaction (RT-PCR)-based test was developed for the specific detection of LMV-Most isolates. Based on the complete genome sequences of three LMV isolates belonging respectively to the Most type, the Common type and neither of these two types, three different assays were compared: (i) presence of a diagnostic restriction site in the region of the genome encoding the variable N-terminus of the capsid protein, in the 3' end of the genome, (ii) RT-PCR using primers designed to amplify a cDNA corresponding to a portion of the P1 coding region, in the 5' end of the genome and (iii) RT-PCR using primers designed to amplify a central region of the genome. The assays were performed against a collection of 21 isolates from different geographical origins and representing the molecular variability of LMV. RT-PCR of the central region of the genome was preferred because its results are expected to be less affected by natural recombination between LMV isolates, and it allows sensitive detection of LMV-Most in situations of single as well as mixed contamination. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: lettuce; potyvirus; LMV; RT-PCR; detection; resistance breaking